(untitled) (Journal of Applied Oral Science, 2021)
The relationship between periodontitis and the pathogenesis of other inflammatory diseases, such as diabetes, rheumatoid arthritis and obesity has been an important topic of study in recent decades. The Th17 pathway plays a significant role in how local inflammation can influence systemic inflammation in the absence of systemic pathology. Objective: To determine Th17 biased-cells in systemically healthy patients in the presence of generalized chronic periodontitis. Methodology: A total of 28 patients were recruited without systemic inflammatory pathology, which was determined by clinical history, the Health Assessment Questionnaire (HAQ) and rheumatoid factor detection. Of these patients, 13 were diagnosed as healthy/gingivitis (H/G) and 15 as generalized chronic periodontitis (GCP). Th17 (CD4+CD161+) cells and Th17IL23R+ (CD4+CD161+IL-23R+) cells were quantified by flow cytometry, based on the total cells and on the lymphocyte region, termed the “enriched population” (50,000 events for each). Results: The percentages of Th17 cells of the H/G and periodontitis groups were similar on total cells and enriched population (19 vs 21.8; p=4.134 and 19.6 vs 21.8; p=0.55). However, Th17IL23R+ cells differ significantly between periodontally healthy patients and generalized chronic periodontitis patients in both total cell (0.22% vs 0.65%; p=0.0004) and enriched populations (0.2% vs 0.75%; p=0.0266). Conclusions: GCP patients (otherwise systemically healthy) were characterized by increased Th17-proinflammatory cell phenotype positive for the IL-23 receptor in peripheral blood. The proportion of Th17 cells that are negative for the IL-23 receptor in the peripheral blood of systemically healthy patients seemed to be unaffected by the presence or absence of chronic periodontitis.